PENGARUH RASIO KEUANGAN TERHADAP KEBIJAKAN DEVIDEN (STUDI PADA PERUSAHAAN REAL ESTATE DAN PROPERTY YANG TERDAFTAR DI BURSA EFEK INDONESIA) - Lisma Aniyati; Hendro Setyono (Jurnal Fokus Manajemen Bisnis, 2017)
This research  aimed to analyze and test the effect of financial ratios of the dividend  policy on the real estate and properties listed in the Indonesia Stock Exchange. The  independent variables is used Return On Investment (ROI), Debt to Total  Assets (DTA),  Earning  Per  Share  (EPS),  and  Total  Asset  Turnover (TATO). Another dependent variable is used dividend Payout Ratio (DPR). The population  of  this  research is 50 companies. There  are  from the  real estate companies and properties  which registered  in Indonesia Stock Exchange in the  period  2012-2014.  Because  not  all  members  of  the  population  is  meet  the criteria,  the  sampling  method  is  used  purposive  sampling  method  there  are  9 samples.  The  analytical  method  are  used  the  classic  assumption  test  and regression test. Based on the survey results showing  that  from  partially there is only  DTA variables  were  not  significantly  influent  to  the  dividend  policy  on  real  estatecompany  and properties  which registered  in Indonesia  Stock Exchange. Another variable  are  ROI, EPS, and TATO  were  significant effect  to  the dividend policy on real estate and properties which registered in Indonesia Stock Exchange. The  results  simultaneous  test  showed  the  ROI,  DTA,  EPS,  and  TATO variables  has  an  influence  to  the  real  estate  company  and  properties  whichregistered in indonesian Stock Exchange. The  higher  coefficient of determination is 49.10%.